The epigenetic mechanisms regulating floral hub genes and their potential for manipulation. (9th November 2021) - Yamaguchi, Nobutoshi
Abstract: Gene regulatory networks formed by transcription factors play essential roles in the regulation of gene expression during plant reproductive development. These networks integrate endogenous, phytohormonal, and environmental cues. Molecular genetic, biochemical, and chemical analyses performed mainly in Arabidopsis have identified network hub genes and revealed the contributions of individual components to these networks. Here, I outline current understanding of key epigenetic regulatory circuits identified by research on plant reproduction, and highlight significant recent examples of genetic engineering and chemical applications to modulate the epigenetic regulation of gene expression. Furthermore, I discuss future prospects for applying basic plant science to engineer useful floral traits in a predictable manner as well as the potential side effects. Abstract : Expression of the floral hub genes is governed by epigenetic mechanisms. This review outlines epigenetic regulatory networks and highlights their potential for modulation by genetic engineering and chemical application.